2009
DOI: 10.1002/dei.256
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of frequency transposition for hearing-impaired school-age children

Abstract: A key objective when fi tting hearing aids to children is to maximize the audibility of high frequency speech cues which are critical in the understanding of spoken English. Recent advances in digital signal processing have enabled the development of hearing aids which offer linear frequency transposition as a new way of accessing these important speech sounds. This study examined the changes in aided performance observed in children with hearing impairment who trialed the alternative hearing aid technology. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 11 publications
0
19
1
Order By: Relevance
“…Additionally, scores after 6 and 3 weeks of training with the FT settings were significantly better than scores with FT at baseline for consonant and vowel recognition at 30 dB HL (see Table 3). Smith et al (2009) found statistically significant differences ( p ≤ .01) on tests of word and phoneme perception for participants using frequency lowering after 12 weeks over previous scores with CP HAs.…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…Additionally, scores after 6 and 3 weeks of training with the FT settings were significantly better than scores with FT at baseline for consonant and vowel recognition at 30 dB HL (see Table 3). Smith et al (2009) found statistically significant differences ( p ≤ .01) on tests of word and phoneme perception for participants using frequency lowering after 12 weeks over previous scores with CP HAs.…”
Section: Resultsmentioning
confidence: 71%
“…Two sets of researchers (Auriemmo et al, 2009; Smith, Dann, & Brown, 2009) studied the use of FT, two (Glista et al, 2009; Wolfe et al, 2010, 2011) investigated NLFC, and one (Miller-Hansen, Nelson, Widen, & Simon, 2003) used FC with DCB. As a result of the heterogeneity (e.g., differences in specific outcome measures used, differences in severity of hearing loss, differences in compression thresholds and stimulus input levels) and small number of included studies for each clinical question, effect sizes were not averaged across studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations